The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/nu11102534
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Characteristics Affect Fetal Growth Response in the Women First Preconception Nutrition Trial

Abstract: The objective of this secondary analysis was to identify maternal characteristics that modified the effect of maternal supplements on newborn size. Participants included 1465 maternal–newborn dyads in Guatemala, India, and Pakistan. Supplementation commenced before conception (Arm 1) or late 1st trimester (Arm 2); Arm 3 received usual care. Characteristics included body mass index (BMI), stature, anemia, age, education, socio-economic status (SES), parity, and newborn sex. Newborn outcomes were z-scores for le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…More specifically, this study demonstrated that maternal anemia at baseline modified the treatment effect for birth outcomes such as birth weight, weight to length ratio as the improvements in these outcomes were significantly greater for Arm 1 (commencing nutrition intervention prior to conception) vs. Arm 2 (commencing same nutrition intervention early in gestation) [11].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…More specifically, this study demonstrated that maternal anemia at baseline modified the treatment effect for birth outcomes such as birth weight, weight to length ratio as the improvements in these outcomes were significantly greater for Arm 1 (commencing nutrition intervention prior to conception) vs. Arm 2 (commencing same nutrition intervention early in gestation) [11].…”
Section: Introductionmentioning
confidence: 74%
“…Anemia is more prevalent in the rural areas of Pakistan, where it is often severe and linked to adverse health consequences such as postpartum hemorrhage, preterm delivery or stillbirth and low birth weight babies [10]. Furthermore, a study conducted by Hambidge et al 2019 found that anemia is an important and potentially modifiable risk factor on birth outcomes among rural Pakistani women [11]. More specifically, this study demonstrated that maternal anemia at baseline modified the treatment effect for birth outcomes such as birth weight, weight to length ratio as the improvements in these outcomes were significantly greater for Arm 1 (commencing nutrition intervention prior to conception) vs.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently completed multi-country trial in which the effects of a comprehensive nutrition intervention initiated prior to conception was compared to the same intervention initiated late in the first trimester (vs. no intervention), birth outcomes, including birth length and weight, LBW, SGA, and stunting, were strongly impacted by the nutritional intervention, with the largest effects in the preconception arm. 35 Nulliparity and preconception anemia were strong effect modifiers of the response to intervention with more modest effects by baseline BMI. 35,36 The WHO global guidance for antenatal care recommends several central nutritional and health interventions for a healthy pregnancy, including multiple micronutrient supplements containing iron-folic acid, calcium supplementation for prevention of preeclampsia in low J o u r n a l P r e -p r o o f intake contexts, and balanced energy and protein supplementation for undernourished populations to reduce low birthweight.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…Similarly, in rural areas of Pakistan anemia is associated with adverse health effects such as postpartum hemorrhage, preterm delivery or stillbirth, and low birth weight babies [ 10 ]. Further, a study conducted by Hambidge et al 2019 found that anemia is a significant and potentially changeable risk factor for birth outcomes among rural Pakistani women in rural Pakistan [ 21 ]. Despite the available data on the burden and magnitude of anemia in rural Pakistan, there is a dearth of literature on understanding the communities’ perceptions about anemia, its causes, consequences, and preventive measures.…”
Section: Introductionmentioning
confidence: 99%